2018
DOI: 10.15171/jpid.2016.008
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of patients toward dental implants as an option in replacing missing teeth: A survey in Kerman, Iran

Abstract: Background. The present study was undertaken to evaluate the level, sources and quality of information on implant treatment as an option for replacement of missing teeth, among a selected sample of dental patients in Kerman, Iran. Methods. A cross-sectional study was conducted on 305 subjects who attended the 6 main dental clinics in Kerman, Iran during January and February 2014. A standardized self-administered closed-ended questionnaire, pretested through a pilot survey, was used in the study. The questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, dental implant treatments are well established amongst patients and routinely performed in Iran. 12 In this study, over half of the students (60% and 65%, respectively) had a positive attitude towards the adequacy of theoretical instructions. In contrast, less than half (50% and 45%, respectively)…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…However, dental implant treatments are well established amongst patients and routinely performed in Iran. 12 In this study, over half of the students (60% and 65%, respectively) had a positive attitude towards the adequacy of theoretical instructions. In contrast, less than half (50% and 45%, respectively)…”
Section: Discussionmentioning
confidence: 60%
“…Chaudhary et al 10 in 2013 evaluated the knowledge and attitude of dental interns about dental implant courses in the state of Karnataka, India, and reported that due to the high cost of implant treatment in India which limits the usage of this treatment as a tooth replacement option, students had poor knowledge about the costs of dental implant treatment. However, dental implant treatments are well established amongst patients and routinely performed in Iran 12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding aligns with another study conducted by AlQahtani [14] , where 58.3% of participants shared the same perception. Esfahani et al [15] also obtained similar results, with 47.4% of individuals expressing a similar viewpoint.…”
Section: Kohli Et Almentioning
confidence: 59%